Effects of Agitation Speed and Reaction Time on Characteristics of Enzymatic Interesterified Products from Red Palm Oil. - Taufik, Moh (2010)
A blend of red palm olein (RPO)/red palm stearin (RPS) and coconut oil (CNO) (82.5:17.7, wt%) was modified by enzymatic interesterification using immobilized lipase from Candida antartica (Novozyme 435) to produce spreads base. Enzymatic interesterification was carried out at 60 and 10% enzyme of the total weight of substrates. The aim of this research was to study the effects of agitation speed and reaction time on characteristics of enzymatic interesterified products. The effects of agitation speed were studied in two different agitation speeds (100 and 200 rpm). The effects of the reaction time were studied in six different reaction times (1, 2, 4, 8, 16 and 24 hours). Comparison of characteristics were carried out between initial mixtures and enzymatic interesterified products by monitoring their carotene contents, slip melting points (SMP), solid fat contents (SFC), moisture contents and free fatty acids (FFA). Results of this study showed that agitation speed and reaction time had effects on characteristics of enzymatic interesterified products. The increasing of agitation speed decreased carotene content and increased SFC and FFA. The increasing of reaction time decreased carotene content and increased SMP, SFC, moisture content and FFA. The carotene contents of enzymatic interesterified products were 149.62-210.05 ppm and the carotene retentions were 70.51-97.79%. The SMP values of enzymatic interesterified products were 30.1‐35.9 , the moisture contents were 0.104-0.143% and the FFA contents were 1.38-4.54%.